Solid-Phase Microextraction Using Poly (1-hexadecene-co-trimethylolpropane trimethacrylate) Coating for Analysis of Pesticides in Tea Samples by High-Performance Liquid Chromatography - Wu, Fang; Chen, Jinghua; Lu, Wanping; Lin, Zian; Zhang, Lan (Current Analytical Chemistry, 2011)
A novel poly (1-hexadecene-co-trimethylolpropane trimethacrylate) coating was prepared and applied as solidphase microextraction (SPME) for analysis of pesticides in tea samples. This SPME coating was fabricated on the surface of fiber by in-situ copolymerization of 1-hexadecene and trimethylolpropane trimethacrylate, in the presence of the ternary porogen (cyclohexanol/1, 4-butanediol/water). Both the effects of porogen ratio and porogen composition on the SPME performance during the polymerization process were investigated. The application of the as-prepared coating was evaluated by extracting residual pesticides in tea samples. Some parameters affecting SPME efficiency such as extraction time, temperature, pH, ionic strength and desorption conditions were examined. Good linearity of the calibration curve was obtained in the range of 1.7-500 ng ml-1 with correlation coefficient (r) better than 0.9957. The detection limits (S/N = 3) for six pesticides were 0.5-5.0 ng ml-1 and the relative standard deviations (RSDs) of precision for one fiber, fiber-tofiber, and day-to-day were 7.0-10.8 %, 4.9-13.3 % and 5.5-12.6 %, respectively (n = 5). Recoveries obtained at spiked tea samples were 80.8-108.8 % for different analytes. The results validated the as-prepared coating had high extraction efficiency toward pesticides as well as good solvent resistant.
Keywords: Linearity